Religious and sexual nationalisms in Central and Eastern Europe: gods, gays and governments - Sremac, Srđan (Religion and the Social Order, 2015)
Contents; Preface. How European is Eastern Europe?; Introduction. The Interplay of Religious and Sexual Nationalisms in Central and Eastern Europe (Sremac and Ganzevoort); Chapter 1. "Faggots Won't Walk through the City": Religious Nationalism and LGBT Pride Parades in Serbia (Mikuš); Chapter 2. European Culture Wars: Sexual Nationalism between Euro-Christian and Euro-Secular Civil Religion in Poland and Romania (Tarta); Chapter 3. For the Sake of the Nations: Media, Homosexuality and Religio-Sexual Nationalisms in the Post-Yugoslav Space (Sremac, Popov Momčinović, Topić, and Jovanović). - Chapter 4. Antagonism in the Making: Religion and Homosexuality in Post-Communist Poland (Hall)Chapter 5. Echoes from the Margin: Responses to the Pope's Statements on Homosexuality in Bosnia & Herzegovina and Sweden (van den Berg and Popov Momčinović); Chapter 6. Religious Nationalism Blocking the Legal Recognition of Same-Sex Unions in the Baltic States (Kilp); Chapter 7. "Gays as a Weapon of the Antichrist": Religious Nationalism, Homosexuality and the Antichrist on the Russian Internet (Dolinska Rydzek and van den Berg). - Chapter 8. Religion, Homosexuality and Nationalism in the Western Balkans: The Role of Religious Institutions in Defining the Nation (Pavasović Trošt and Slootmaeckers)Contributors